2017
DOI: 10.18632/oncotarget.17605
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and efficacy of tumor-targeting Salmonella typhimurium A1-R compared to VNP 20009 in a syngeneic mouse tumor model in immunocompetent mice

Abstract: Salmonella typhimurium A1-R (S. typhimurium A1-R) attenuated by leu and arg auxotrophy has been shown to target multiple types of cancer in mouse models. In the present study, toxicologic and biodistribution studies of tumor-targeting S. typhimurium A1-R and S. typhimurium VNP20009 (VNP 20009) were performed in a syngeneic tumor model growing in immunocompetent BALB/c mice. Single or multiple doses of S. typhimurium A1-R of 2.5 × 105 and 5 × 105 were tolerated. A single dose of 1 × 106 resulted in mouse death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Although KST0650 was highly attenuated, it preferentially accumulated in tumor cells in vivo, which was almost comparable with the levels of other well-known cancer targeting strains, such as VNP20009, SL∆ppGpp (∆relA∆spoT), and A1-R 13,18,45 . Despite it could effectively target, colonize, invade tumors, and reduce tumor growth rate slightly as compared with PBS only, which helps prolong mice survival, its tumor-curing effect was not observed obviously in a tumor-bearing mouse model, suggesting that KST0650 monotherapy does not show anti-tumor effect effectively.…”
Section: Discussionmentioning
confidence: 57%
“…Although KST0650 was highly attenuated, it preferentially accumulated in tumor cells in vivo, which was almost comparable with the levels of other well-known cancer targeting strains, such as VNP20009, SL∆ppGpp (∆relA∆spoT), and A1-R 13,18,45 . Despite it could effectively target, colonize, invade tumors, and reduce tumor growth rate slightly as compared with PBS only, which helps prolong mice survival, its tumor-curing effect was not observed obviously in a tumor-bearing mouse model, suggesting that KST0650 monotherapy does not show anti-tumor effect effectively.…”
Section: Discussionmentioning
confidence: 57%
“…Salmonella typhimurium A1‐R ( S. typhimurium A1‐R ) attenuated by leu and arg auxotrophy has been shown to target multiple types of cancer in mouse models . We used the Gene Pulser Transfection Apparatus (Bio‐Rad, 1652100, California, USA) to transfer plasmids into competent attenuated S. typhimurium .…”
Section: Methodsmentioning
confidence: 99%
“…Salmonella typhimurium A1-R (S. typhimurium A1-R) attenuated by leu and arg auxotrophy has been shown to target multiple types of cancer in mouse models. 13 We used the Gene Pulser Transfection Apparatus (Bio-Rad, 1652100, California, USA) to transfer plasmids into competent attenuated S. typhimurium. The instructions indicated that the electrophoretic conditions for attenuated S. typhimurium were the same as for E. coli, so we performed the test according to section 6.1 (E. coli) in the instructions.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…First approaches aimed to passage Salmonella through cancerous tissue either in vitro or in vivo to improve tumour-targeting by selection. This strategy resulted in the prominent Salmonella vector strains VNP20009 and A1-R (Low et al, 2004;Zhao et al, 2006;Zhang et al, 2017). VNP20009 was evaluated in clinical trials.…”
mentioning
confidence: 99%
“…The Salmonella variant A1-R, on the other hand, appears to be highly potent. This strain is deficient for the amino acids arginine and leucine and has shown great promise in many different types of murine tumours and patient-derived orthotopic xenografts (Hoffman, 2016;Zhang et al, 2017). It will be interesting to follow this particular strain and its performance in clinical trials with human cancer patients.…”
mentioning
confidence: 99%